Adapting Green Innovation Centres to climate change: analysis of value chain adaptation potential. Maize, rice, potato, and cassava value chains in Oyo, Ogun, Benue, Nasarawa, Plateau, Kano, and Kaduna states, Nigeria - Alliance of Bioversity International and CIAT; CGIAR Research Program on Climate Change, Agriculture and Food Security; Deutsche Gesellschaft für Internationale Zusammenarbeit (2020)
The present report aims to provide a climate and vulnerability analysis of the Green Innovation Centres (GIC) target commodity value chains. Herein we identify climate change- related vulnerabilities, hazards, and opportunities for adaptation to the same. Ultimately, our goal is to foster awareness of risks and adaptation priorities in the selected value chains and inform climate investments and planning through the recommendations on priority innovations to manage climate risks.